Structural and Functional Brain Abnormalities in Internet Gaming Disorder and Attention-Deficit/Hyperactivity Disorder: A Comparative Meta-Analysis - Gao, Xinyu; Zhang, Mengzhe; Yang, Zhengui; Wen, Mengmeng; Huang, Huiyu; Zheng, Ruiping; Wang, Weijian; Wei, Yarui; Cheng, Jingliang; Han, Shaoqiang; Zhang, Yong (Frontiers in Psychiatry, 2021)
Background: Patients with Internet gaming disorder (IGD)and attention-deficit/hyperactivity disorder (ADHD) had high comorbidity but it is still unknown whether these disorders have shared and distinctive neuroimage alteration. Objective: The aim of meta-analysis is to identify shared and disorder-specific structural, functional and multimodal abnormalities between IGD and ADHD. Methods: Systematic literature search was conducted for whole-brain voxel-based morphometry (VBM) and functional magnetic resonance imaging (fMRI) studies of comparing people with IGD or ADHD with healthy controls. Regional gray matter volume (GMV) and fMRI differences were compared in patient group and then a quantitative comparison was performed to find abnormalities (relative to controls) between IGD and ADHD using seed-based d mapping meta-analytic methods. Result: The meta-analysis contained 14 IGD VBM studies (contrasts covering 333 IGDs and 335 HCs), 26 ADHD VBM studies (1051 patients with ADHD and 887 controls), 30 IGD fMRI studies (603 patients with IGD and 564 controls) and 29 ADHD fMRI studies (878 patients with ADHD and 803 controls). Structurally, VBM analysis showed disorder-specific GMV abnormality in the putamen among IGD subjects and orbitofrontal cortex in ADHD, and shared GMV in the prefrontal cortex and striatum. Functionally, fMRI analysis discovered that IGD-differentiating increased activation in the precuneus and shared abnormal activation in anterior cingulate cortex, insular and striatum. Conclusion: IGD and ADHD have shared and special structural and functional alterations. IGD have disorder-differentiating structural alterations in putamen and ADHD are in the orbitofrontal cortex. Disorder-differentiating fMRI activation were predominantly observed in the precuneus among IGD subjects and shared impairing function connection is in rewards circuit (including ACC, OFC and striatum).